Financialisation vs. Development Finance: the Case of the Post-Crisis Argentine Banking System - Alan Cibils; Cecilia Allami (Revue de la Régulation)
The end of the Bretton Woods era and the emergence of neoliberal economics resulted in profound transformations in domestic economies and international economic relations. The keystone of these transformations was the liberalisation of domestic and international financial markets. Faulty theoretical foundations and the resulting catastrophic policy failures prompted a vast literature by critical economists on the international financial architecture and domestic financial structures best suited for economic development. In recent decades, debate has also centred on what has been labelled “financialisation”, i.e. the increasingly central role played by financial markets and transactions in economic activity. In this paper we try to ascertain whether Argentina experienced a process of financialisation between 1990 and 2009 and what impact, if any, it has had on Argentine banking. We conclude that there has been a strong process of financialisation in Argentina in the post 2001-2002 crisis period. We also explore in a preliminary fashion potential reasons behind Argentine post-crisis financialisation. The paper concludes by suggesting that it is time to consider alternative banking arrangements if development finance is to become a policy priority.